Android-Based Learning Media Designed with Figma for Mechanical Measuring Instruments in Vocational Automotive Education - Arga Farid Ahmadi; Setyo Bhahak Fendi Baihaqi; Rizqi Fitri Naryanto (AEEJ : Journal of Automotive Engineering and Vocational Education, 2026)
Repetitive and conventional learning can make mechanical measuring instrument topics difficult for vocational students to understand. This study developed and initially evaluated Android-based learning media designed with Figma for Mechanical Measuring Instruments. The research used the ADDIE development model with a pre-experimental one-group pretest–posttest design involving Grade X TKRO students. Product feasibility was assessed by media and material experts, while learning outcomes were examined through pretest, posttest, t-test, N-Gain, and student responses. The media expert score was 85.4%, and the material expert score was 90.8%, both in the very feasible category. The average score increased from 43.6 in the pretest to 80.2 in the posttest. The reported t-test value was 44.892 > 2.026, with an N-Gain of 0.67, indicating moderate improvement. Student responses reached 86.5%, categorized as very good.